Konseling Kelompok Analisis Transaksional untuk Mengurangi Kecemasan Berbicara di Depan Umum: Array - Maghfirah Hidayani; Netrawati; Yeni Karneli (eductum: Jurnal Literasi Pendidikan, 2022)
Currently, there are many students who experience anxiety in public speaking. Meanwhile, public speaking is a skill that is needed by students, especially in the world of education. This speaking ability is needed so that students can convey what we feel and what we think, so that the ability to speak must be developed and also improved, as well as public speaking. In fact, not all individuals can have the ability to speak in public, because there are several obstacles experienced by individuals, one of which is anxiety in speaking. Anxiety about speaking itself is called reticence, an individual's inability to develop a conversation that is not caused by a lack of knowledge but due to the inability to convey messages perfectly, which is characterized by psychological and physiological reactions. The purpose of this study is to help individuals reduce public speaking anxiety by using a group approach. The type of research used is a literature study by utilizing articles and journals related to group counseling using transactional analysis to deal with anxiety in public speaking. The findings of this study reveal that using a transactional approach can help individuals to reduce anxiety in public speaking. One of the techniques used is speaking practice in group forums.